Land mobile radio equipment - Specifications (Second revision) - Abdullah, Khaizuran; Ismail, Ahmad Fadzil; Ahmad, Mohd Shukur (Malaysian Communications and Multimedia Commission, 2025)
In exercise of the power conferred by Section 184 of the Act, the Commission has designated the Malaysian Technical Standards Forum Bhd (‘MTSFB’) as a Technical Standards Forum which is obligated, among others, to prepare the technical code under Section 185 of the Act.